ZnWO(4) Nanoparticle Scintillators for High Resolution X-ray Imaging - Jeong, Heon Yong (Nanomaterials (Basel), 2020)
The effect of scintillator particle size on high-resolution X-ray imaging was studied using zinc tungstate (ZnWO(4)) particles. The ZnWO(4) particles were fabricated through a solid-state reaction between zinc oxide and tungsten oxide at various temperatures, producing particles with average sizes of 176.4 nm, 626.7 nm, and 2.127 μm; the zinc oxide and tungsten oxide were created using anodization. The spatial resolutions of high-resolution X-ray images, obtained from utilizing the fabricated particles, were determined: particles with the average size of 176.4 nm produced the highest spatial resolution. The results demonstrate that high spatial resolution can be obtained from ZnWO(4) nanoparticle scintillators that minimize optical diffusion by having a particle size that is smaller than the emission wavelength.